ANALYSIS METHOD OF GRADUAL CAST INSITU PROJECT COMPLETION OVERPASS PT. TALENTA BUMI MARABAHAN - Akhmad Fitriadi (CERUCUK, 2021)
Overpass project development Marabahan is a CSR (Corporate Social Responsibility) from PT. Talenta Bumi, namely making public care facilities for the security and facilitate road transport and to improve the welfare of society .This project Overpass consists of main bridge prestressed concrete girders with spans of 30 m and bridges using slab pile construction with a total length of 200 m. This study aims to determine the calculation method of the analysis of in situ casts gradually and to determine the method of implementation of the phased-situ cast on Marabahan Overpass project.Analysis of cast insitu method stages in the project completion Overpass PT. Marabahan Earth's talents will be obtained security calculations on the structure of the Overpass. Foundry work first is casting with cast in situ on the crown, after it's done casting method cast in situ stages at the slab to be divided into two stages, namely the first layer 20 cm (half slab) and the second layer 15 cm (top slab) using scaffolding as a scaffold and job formwork with main reinforcement ɸut 22-150 which gradually cast directly on the ground with the popularity chart Fc validation test cylinder '30 MPa and graphs coefficient of concrete strength PBI age 71. For loading on board, the work scaffolding (scaffolding) at the time of cast insitu gradually in the field wearing a scaffold with a heavy load capacity (heavy duty) has a maximum load of 675 kg/bay or 0.675 tons/m2, and using strong wooden scaffolding with wood class III based voltage PKKI 1961 timber permit.Based on the analysis results of calculations using the method of cast insitu gradually, by doing a test trial error with conditional on calculation of security moment of the plan should be greater than the moment of ultimate, then casting the first layer half slab in getting workable with the concrete less than one day the Fc '5 MPa and to stage a second layer using a comparison chart coefficient PBI age compressive strength, obtained Fc' 9.57 MPa to 1.5 days workmanship of the concrete casting. With the trial based on the test results of the concrete age, can accelerate and cut time jobs and can save the cost of the work, such as the cost of the use of formwork and scaffolding usage. suggestednecessary to test the concrete test cylinders for 1 day, 2 days, 3 days, etc,so that getting the maximum test.